IMPLEMENTASI E-KINERJA DALAM MENINGKATKAN PRODUKTIVITAS KERJA DI BAPPEDA KABUPATEN NAGAN RAYA - Maulana Andika; Desi Maulida (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2022)
E-Kinerja is an electronic system arising from the accelerated development of increasingly sophisticated communication and technology. This study aims to identify, analyze and assess the application of new technology as an effort to increase the effectiveness and productivity of PNS/ASN performance in work activities through the use of e-performance. This research is a type of qualitative research with a case study method presented with descriptive data in the form of interviews from informants, field observations and studies of documents related to objects. The results showed that the implementation of E-Kinerja to increase the productivity of civil servants' performance in BAPPEDA Nagan Raya Regency was not yet effective in increasing the productivity of employee performance, but only to increase the level of discipline on time with the level of adaptation to the use of sustainable E-Kinerja applications. In accordance with the concept used by researchers, namely the criteria for successful implementation of the aspect of ensuring productivity and performance analysts. The implementation of e-Kinerja is also faced with several obstacles, including the lack of ability of employees to adopt new innovations or, lack of IT/ICT experts, lack of facilities and infrastructure, and the absence of regulations governing the implementation of E-Kinerja specifically. Therefore, periodic technical guidance is needed with a focus on routine discussions, appointing one of the experts as E-Kinerja admin and providing a more stable internet network.